Socioeconomic and Demographic Disparities in Knowledge of Reproductive Healthcare among Female University Students in Bangladesh - Md. Nazrul Islam Mondal, PhD; Md. Monzur Morshad Nasir Ullah, MSc; Md. Nuruzzaman Khan, MSc; Mohammad Zamirul Islam, PhD; Md. Nurul Islam, PhD; Sabiha Yasmin Moni, MBBS, MPhil; Md. Nazrul Hoque, PhD; Md. Mashiur Rahman, MSS (Global Health and Education Projects, Inc., 2016)
Background: Reproductive health (RH) is a critical component of women's health and overall well-being around the world, especially in developing countries. We examine the factors that determine knowledge of RH care among female university students in Bangladesh. Methods: Data on 300 female students were collected from Rajshahi University, Bangladesh through a structured questionnaire using purposive sampling technique. The data were used for univariate analysis, to carry out the description of the variables; bivariate analysis was used to examine the associations between the variables; and finally, multivariate analysis (binary logistic regression model) was used to examine and fit the model and interpret the parameter estimates, especially in terms of odds ratios. Results: The results revealed that more than one-third (34.3%) respondents do not have sufficient knowledge of RH care. The X2 -test identified the significant (p < 0.05) associations between respondents' knowledge of RH care with respondents' age, education, family type, watching television; and knowledge about pregnancy, family planning, and contraceptive use. Finally, the binary logistic regression model identified respondents' age, education, family type; and knowledge about family planning, and contraceptive use as the significant (p < 0.05) predictors of RH care. Conclusions and Global Health Implications: Knowledge of RH care among female university students was found unsatisfactory. Government and concerned organizations should promote and strengthen various health education programs to focus on RH care especially for the female university students in Bangladesh. Key words: Reproductive Health Care • Contraceptive Use • Family Planning • Women's Health • Female University Students • Bangladesh Copyright © 2015 Mondal et al. This is an open-access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.